Hydrobiological studies within the tea gardens at Srimangal, Bangladesh. V. Desmids (Euastrum, micrasterias, actinotaenium and cosmarium) - Islam, AKM Nurul; Irfanullah, Haseeb Md (Bangladesh Journal of Plant Taxonomy, 2006)
Ninety-three desmid taxa belonging to four genera, namely Euastrum, Micrasterias, Actinotaenium and Cosmarium have been recorded from different aquatic habitats located within the tea gardens at Srimangal, Maulvi Bazar. Of these, 20 are described as new records for Bangladesh, including a new variety, E. substellatum Nordst. var. bangladeshicum Islam & Irfanullah var. nov. and a new forma, Cosmarium depressum (Näg.) Lund. var. apertum (Turner) Hirano fa. spinosum Islam and Irfanullah fa. nov. Key words: acidic habitats, species diversity, phytoplankton, desmids, new taxa, new records DOI: 10.3329/bjpt.v13i1.589 Bangladesh J. Plant Taxon. 13(1): 1-20, 2006 (June)